(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Today, great progress is being made in the development of pharmacology, and the spheres of influence on the human body are also showing good results. What is pharmacology? Is it a disease or a medical science? What is the history of who discovered it? What are the effects on the human body after a patient consumes pharmacological drugs?